Pengolahan Air Sungai Gambut Dengan Metode Filtrasi - Hartini, Eko; Erawati, Erni; Aryani, Lenci (Dian Nuswantoro Semarang, 2023)
The people of Teluk Pulai Village use the water of the Red River, which is peat water, as a source of clean water. Not all residents use the water because it is brown to reddish in color. The results of the water test show that the turbidity parameter is 37 NTU, the iron (Fe) content is 4.57 mg/L, and the manganese (Mn) content is 2.39 mg/L; therefore, it is necessary to treat the water so that it is suitable as clean water and raw water for drinking water. The purpose of this study was to determine the effect of media thickness and contact time on reducing turbidity, pH, temperature, Fe content, and Mn content in river water by filtration. The research design was an experiment with a pretest-posttest design with one control group and six replications. The independent variables were media thickness of 20 and 40 cm and contact time of 5 and 10 minutes, while the dependent variables were turbidity, pH, temperature, Fe content, and Mn content. The data obtained were analyzed descriptively based on Permenkes No. 32 of 2017. The results of the initial measurement of turbidity, Fe, and Mn levels before each treatment were above the quality standard according to Permenkes No. 32 of 2017. After processing using the filtration method, the results were in accordance with the quality standards, namely turbidity < 1 to 4 NTU, pH 6.5–6.9, temperature 25.8–26.4 oC, Fe content 0.024-0.126 mg/L, and Mn content 0.31–1.78. Although maximum effectiveness is achieved with a thickness of 40 cm and a contact time of 10 minutes, it is economically advisable for the community to treat river water using zeolite and activated sand filtration media with a thickness of 20 cm and a contact time of 5 minutes.